Case report of a type II single umbilical artery seen in the first trimester anomaly scan (Indian Journal of Case Reports, 2024)
Umbilical arteries normally originate from a pair of allantoic arteries. Obliteration or non-formation of any of the two umbilical arteries gives rise to a single umbilical artery (SUA). 0.5–1% of fetuses show the presence of a SUA. A rarer abnormality is when a SUA is found originating from the abdominal aorta, representing the persistent vitelline artery. Such an anomaly is termed Type II SUA. Here, we present a case of Type II SUA in a 30-year-old first trimester gravid female. Obstetric ultrasound done in the first trimester showed non-visualization of the umbilical arteries adjacent to the urinary bladder. Instead, an aberrant, large vessel was seen tracking anteriorly from the aorta towards the umbilical cord. The aorta distal to the origin of this aberrant vessel appeared hypoplastic.